Hey there!!
First equation :
Given equation :
... 2 ( n + 1 ) + 1 = ( n - 5 ) + ( n - 2 )
Excluding the parenthesis and using the distributive property :
... 2n + 2 + 1 = n - 5 + n - 2
Combining all the like terms on each side :
... 2n + 3 = 2n - 7
Subtracting 2n and subtracting 3 on both sides :
... 0 = -10
Hence, the first equation has "zero" values.
Second equation :
Given equation :
... 3 ( n - 1 ) - 2 = 4 ( n - 4 ) - ( n - 1 )
Using the distributive property :
... 3n - 3 - 2 = 4n - 16 - n + 1
Combining all the like terms :
... 3n - 5 = 3n - 15
Adding 5 and subtracting 3n on both sides :
... 0 = -10
Hence, the second equation has "zero" values.
Hope my answer helps!!